Impaired wrist position sense is linked to motor abnormalities in young adults with a probable developmental coordination disorder. (16th February 2022) - Tseng, Yu-Ting; Lin, Yi-Hsuan; Chen, Yi-Wen; Tsai, Chia-Liang; Chen, Fu-Chen
Highlights: Young adults with probable DCD are associated with proprioceptive deficits. Young adults with probable DCD exhibit reduced wrist position sense precision. Decreased wrist proprioceptive precision is associated with body coordination. Somatosensory and motor deficits are likely to persist into adulthood. Abstract: Proprioceptive deficits have been found to underlie motor abnormalities in individuals with movement disorders. This study investigated wrist proprioceptive acuity in young adults with and without probable developmental coordination disorder (DCD) and examined how proprioceptive acuity is linked to different domains of motor function. Thirty participants were included in this study (age, 19–22 years), ten with probable DCD and 20 controls. Wrist proprioceptive acuity was assessed using a joint position sense paradigm under contralateral and ipsilateral conditions. The Bruininks − Oseretsky Test of Motor Proficiency 2nd Edition (BOT-2) was used to measure different domains of motor ability. Compared to the control group, young adults with probable DCD exhibited significantly increased proprioceptive error variability in contralateral ( p < 0.0001) and ipsilateral conditions ( p < 0.05). Furthermore, wrist proprioceptive error variability was significantly associated with the levels of body coordination measured by BOT-2 ( r = − 0.55). This study verified impaired wrist proprioceptive function in young adults with probable DCD, which is likely to contribute to motor impairment in adults with DCD.